Co-limitation toward lower latitudes shapes global forest diversity gradients - liang, Jingjing; Gamarra, Javier G.P.; Picard, Nicolas; Zhou, Mo; Pijanowski, Bryan; Jacobs, Douglass F.; Reich, Peter B.; Crowther, Thomas W.; Nabuurs , Gert-Jan; de-Miguel, Sergio; Peri, Pablo Luis; Hui, Cang (Springer Nature, 2022)
The latitudinal diversity gradient (LDG) is one of the most recognized global patterns of species richness exhibited across a wide range of taxa. Numerous hypotheses have been proposed in the past two centuries to explain LDG, but rigorous tests of the drivers of LDGs have been limited by a lack of high-quality global species richness data. Here we produce a high-resolution (0.025° × 0.025°) map of local tree species richness using a global forest inventory database with individual tree information and local biophysical characteristics from ~1.3 million sample plots. We then quantify drivers of local tree species richness patterns across latitudes. Generally, annual mean temperature was a dominant predictor of tree species richness, which is most consistent with the metabolic theory of biodiversity (MTB). However, MTB underestimated LDG in the tropics, where high species richness was also moderated by topographic, soil and anthropogenic factors operating at local scales. Given that local landscape variables operate synergistically with bioclimatic factors in shaping the global LDG pattern, we suggest that MTB be extended to account for co-limitation by subordinate drivers.